P19 Tracking treatment response in severe asthma using a novel assessment of lung inhomogeneity. (12th November 2019) - Smith, NMJ; Talbot, NP; Ritchie, GAD; Pavord, ID; Robbins, PA; Petousi, N
Abstract : Background: In asthma, physiological assessments are not always concordant with disease control e.g. symptoms, exacerbations, treatment response or the presence of underlying inflammation. In this study, we sought to investigate whether a novel technique that quantifies inhomogeneity in the lung can provide a sensitive physiological measure that can track response to treatment and change in disease inflammation in patients with severe asthma. Preliminary data are reported. Methods: Six patients with severe asthma on Step 4 treatment, with Type-2 high disease (high FeNO >50 ppb and eosinophilic inflammation with blood eosinophil count >350/ml) were studied at baseline, at 1 week following a FENO suppression test (high-dose inhaled steroids >1000 mcg fluticasone daily) and at 1 month following systemic steroids (80 mg intramuscular triamcinolone). The technique involves a nitrogen-washout protocol (10 min air-breathing, 5 min 100% oxygen-breathing) using a novel highly-accurate in-airway gas analyser that uses laser absorption spectroscopy to measure respired gases every 10 ms; a novel mathematical model is then fitted to the gas-exchange data to obtain a distribution of lung compliance relative to lung volume. The standard deviation of the distribution (σCL:VA) provides a measure of regional variation in lung compliance. Results: The patients had a negative FeNO suppression test (i.e. had <40% reduction in FeNO), indicating ongoing airways inflammation that is refractory to inhaled corticosteroids, and therefore went on to receive a triamcinolone injection. σCL:VA was elevated at baseline in these patients at 0.94±0.19 (mean ±SD), compared with healthy controls (0.47±0.09, n=23), indicating significant inhomogeneity. Following the FeNO suppression test, there was no significant change in σCL:VA (0.84±0.12). In contrast, at 1 month following triamcinolone treatment, there was a significant reduction in σCL:VA down to 0.65±0.14 (paired t-test, p<0.0005; figure 1), which was concordant with changes in markers of inflammation (eosinophil count and FeNO). Conclusion: These preliminary data suggest that σCL:VA may be a sensitive marker of treatment response in patients with asthma, that tracks disease inflammation. This may be useful in patients with non T2-high asthma too, in which inflammatory biomarkers are not available.